A Monte-Carlo study on the fluorescent nuclear track detector (FNTD) response to fast neutrons: Which information can be obtained by single layer and 3D track reconstruction analyses?. (July 2021) - Stabilini, A.; Kiselev, D.; Akselrod, M.S.; Yukihara, E.G.
Abstract: Fluorescence Nuclear Track Detectors (FNTDs) are part of a new technology developed for particle detection and applicable to personal neutron dosimetry. The objective of this study is to simulate the FNTD fast neutron response to: (i) assess and understand the performance of the existing neutron dosimeter design (Landauer Inc.) and its associated single layer track-spots analysis; and (ii) evaluate the potential information that can be obtained by the analysis of the 3D reconstructed recoil proton trajectories. To achieve that, a FLUKA Monte Carlo (MC) model of the current FNTD design was developed and the FNTD response was investigated for mono-energetic neutrons and the 252 Cf and 241 AmBe neutron sources. The investigation of the recoil proton densities behind the different converters showed that the single layer analysis and dose calculation algorithm, based on the comparison and subtraction of the track densities behind the different converters, works properly only up to neutron energies 13 MeV. Above this neutron energies, recoil protons generated in the detector housing (PE) have a range larger than the thickness of the PTFE and 6 Li-enriched glass, reaching the FTND and, therefore, adding to the signal in these detection regions and influencing the secondary electron discrimination and the energy determination algorithm. MC simulations show that the FNTD 3D reconstructed recoil proton tracks can provide estimates of the irradiation angles and average neutron energy. The results show that the angle or displacement (dX/dZ or dY/dZ) distributions of the recoil proton tracks can be used to obtain information on irradiation angle; the angle with the detector's normal (polar angle), the most important because of its influences on the FTND sensitivity, can be determined in laboratory and for irradiation angles < 60° with an 4° uncertainty already for doses > 4.5 mSv in the case of a 214 AmBe neutron irradiation. The neutron field mean energy can also be determined for normal irradiation by analysing the depth distribution of the recoil proton tracks already for a minimum of 150 tracks, or 2.5 mSv for 241 AmBe, assuming a scanned area is 2.0 mm 2 . Therefore, the present study contributes to understanding the performance of the current FNTD design and analysis for neutron dosimetry and investigates a new detector evaluation approach to gain additional information on the irradiation conditions. Highlights: A Monte-Carlo model of the FNTD fast neutron response was developed. Evaluation approach based on single layer is reliable for neutron energies <13 MeV. For neutrons energies >13 MeV another analysis or detector design shall be adopted. 3D recoil proton tracks indicate the direction and mean energy of the radiation.